Effects of Valence and Emotional Intensity on the Comprehension and Memorization of Texts - Megalakaki, Olga; Ballenghein, Ugo; Baccino, Thierry (Frontiers in Psychology, 2019)
In the present study, we independently manipulated valence (positive, negative or neutral) and emotional intensity (low, medium or high), asking what impact they have on text comprehension (via surface, paraphrase and inference questions) and memorization (via Remember/Know test) in adults. Results show that emotional contents, including valence and intensity affects comprehension. Emotional valence had a significant effect on text comprehension, with higher scores for positive and neutral texts than for negative ones. Participants scored higher on the surface questions for positive texts and on the inference questions for negative texts, with equivalent scores for paraphrase questions. Regarding emotional intensity, medium intensity generally fostered better comprehension of both positive and negative texts. High emotional intensity is beneficial for positively valenced texts, but hinders the understanding of negatively valenced ones. Regarding memorization, participants recalled more emotional words than neutral ones, and more words for positive texts than for either negative or neutral ones. In conclusion, our results show that emotions play an important role and improve the processing of information.